Applied cell and molecular biology for engineers [ - Waite, Gabi Nindl; Waite, Lee (McGraw-Hill, 2007)
Presents engineering concepts that foster better machines and procedures in the health field. This resource provides you with a foundation in the biological sciences and the quantitative analysis.